Penilaian aliran limbah elektronika di DKI Jakarta menggunakan Material Flow Analysis (MFA) - Dino Rimantho; Erliza Noor; Eriyatno Eriyatno; Hefni Effendi (School of Postgraduate Studies, Diponegoro Univer, 2019)
Electronic equipment is produced to meet human needs, so this will also have a significant impact on increasing the rate of e-waste generation in landfills in almost all countries. One of the environmental pollution issues that are of concern throughout the world is the management of e-waste (e-waste). This is due to the rapid increase in the use of electronic products. Thus, the existence of electrical and electronic equipment becomes shorter and becomes obsolete. The absence of information related to the volume of e-waste generation and material flow is one of the problems of the Indonesian government in managing e-waste. Therefore, the purpose of this paper is to calculate e-waste and analyze material flow. The method used in this study is Material Flow Analysis (MFA). Furthermore, a survey of household and informal sector respondents was used. The questionnaire adopted from UNEP was modified and distributed to 400 households and 54 informal sectors in DKI Jakarta. The results show the total rate of generation of e-waste produced aaproximately 7713.42013 kg/year. Furthermore, it is necessary to develop several strategies in order to avoid negative impact. This research can be information in filling the data limitations and management of sustainable e-waste in DKI Jakarta.